PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN PROMOSI PRODUK SAFI TERHADAP MINAT BELI KONSUMEN ( Studi Pada Wanita Usia 20-30 Tahun di Yogyakarta) - Hamidah, Diana Rofi; Giyartiningrum, Eko (Journal Competency of Business, 2023)
This research aims to know: (1) the influence of brand image toward buying interest, (2) the influence of product quality toward buying interest, (3) the influence of promotion toward buying interest, (4) the influence of brand image, products quality, and promotion toward buying interest. This research applied a quantitative approach by collecting data through survey methods. The population of this research is women aged 20-30 years in Yogyakarta. The sample consisted of 30 respondents by collected data through a questionnaire. The data analysis technique in this study used multiple linear regression analysis. The results of this research showed that: (1) brand image has a positive impact on buying interest, and (2) product quality has a positive impact on buying interest. (3) promotion gives positive impact on buying interest, (4) brand image, products quality, and promotion simultaneously give positive impact on buying interest.